A Business Model for ALL solutions - Realinho, J.; O'Neill, Henrique (Ambient Assisted Living: From Technology to Intervention, 2015)
Ambient Assisted Living as a concept refers to intelligent systems of assistance for a better, healthier and safer life in the preferred living environment and covers products and services that interconnect Information and Communication Technologies (ICT) and the social environment. This will be particularly useful to the growing number of seniors especially in Europe. The AAL4ALL project, sponsored by 34 national entities, aims to develop an ecosystem of products and services for Ambient Assisted Living associated to a business model and validated through large scale trial. This paper focus on identifying the business model associated to this ecosystem and all of its stakeholders. It was found that there is a need to create a central entity that promotes the cooperation of the various partners and find ways of commercializing these types of products and services through the use of ICT. With this being said, three possible implementation methods are established including a business plan associated to each one of these methods.